2018
DOI: 10.1111/ajag.12522
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and the health of older people in Australia: A scoping review on the role of mobile applications (apps) in ameliorating impact

Abstract: This study demonstrates that there is a gap in the evidence about the mobile apps designed for healthy ageing and, more specifically, to improve access to the external environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Future trends, from a technological perspective, combine gamified learning with mobile learning; with VR/AR; with intelligent bodies; with brain science; with artificial intelligence and big data (Quelly et al, 2016;Black et al, 2018). If the research is to solve students' learning problems through mobile games, it is necessary to combine various research results and educational results from game design.…”
Section: Future Trends and Limitations In Educational Mobile Gamesmentioning
confidence: 99%
“…Future trends, from a technological perspective, combine gamified learning with mobile learning; with VR/AR; with intelligent bodies; with brain science; with artificial intelligence and big data (Quelly et al, 2016;Black et al, 2018). If the research is to solve students' learning problems through mobile games, it is necessary to combine various research results and educational results from game design.…”
Section: Future Trends and Limitations In Educational Mobile Gamesmentioning
confidence: 99%
“…The ageing of Australia's population is accompanied by increasing exposure to environmental stressors 1 . Previous research demonstrated that the ageing of the population is increasing in parallel with rising temperatures, and evidence shows older people do not cope as well with environmental stressors 2 .…”
Section: Introductionmentioning
confidence: 99%